Design And Fabrication Of Flexible Strain Sensor For Food Packaging - Abdul Aziz, Siti Nuha Majiddah (Universiti Sains Malaysia, 2022)
The work in this thesis was focused in developing a flexible strain sensor capable of detecting strain within the low working range for the use in food packaging. For this cause, capacitive pressure sensors was designed, fabricated and characterised, utilising conductive and non-conductive polymeric elements to sense loads. An interdigital capacitive strain sensor was developed, which successfully provided a high reading. The sensor employ polydimethylsiloxane (PDMS) layers which act as the substrate and dielectric layer that sandwich the electrode layer. To fabricate these PDMS layers, a drop casting process was done involving a 3D printed mould in order to create a rectangular shaped PDMS. The electrode was also drop casted on the pattern that was on top of the substrate and subsequently dielectric layer was added. The fabricated flexible strain sensor shows initial capacitance as high as 4.98 pF. The presented capacitive strain sensor offers a reasonable capacitance; therefore; it can be utilised in the food packaging as well as other application that also need a measurement of strain. This design of strain sensor is chosen as its ease of design.